El baño ecológico seco en la vivienda saludable en Nueva Rinconada, San Juan de Miraflores - Márquez, Patricia (2022)
In this article, the dry ecological toilet and its incidence in healthy housing are explored, in Lima´s peri-urban context. For this, the study categories are: operation, excreta´s hygienic disposal, environmental protection, family health, among others. The theoretical basis of Uno Winblad et al (2004) was chosen as the reference framework with the most empirical evidence regarding ecological sanitation. The description of the problem, the history, related research and the theoretical and scientific structure that supports the study are reviewed and the objectives of the research are proposed, in addition a qualitative methodology that allows the analysis of the results of in-depth interviews to users of ecological dry toilets in their homes. In general terms, the results exhibited that the greatest benefit of the dry ecological toilet in the healthy home is the excreta´s hygienic elimination, which leads to a series of conclusions and recommendations.